Women’s symbolic prisons-agencies: a Latin American-Middle Eastern dialogue - (:unkn) unknown (My University, 2026)
The project aims to answer the following question: What are the symbolic prisons for women in the Global South? How does the colonial-modern-patriarchal-capitalist matrix of oppression configure punitiveness and injustice while installing symbolic prisons